2006
DOI: 10.1083/jcb.200508116
|View full text |Cite
|
Sign up to set email alerts
|

A role for the RabA4b effector protein PI-4Kβ1 in polarized expansion of root hair cells in Arabidopsis thaliana

Abstract: The RabA4b GTPase labels a novel, trans-Golgi network compartment displaying a developmentally regulated polar distribution in growing Arabidopsis thaliana root hair cells. GTP bound RabA4b selectively recruits the plant phosphatidylinositol 4-OH kinase, PI-4Kβ1, but not members of other PI-4K families. PI-4Kβ1 colocalizes with RabA4b on tip-localized membranes in growing root hairs, and mutant plants in which both the PI-4Kβ1 and -4Kβ2 genes are disrupted display aberrant root hair morphologies. PI-4Kβ1 inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
326
3
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(355 citation statements)
references
References 44 publications
22
326
3
4
Order By: Relevance
“…These observations indicate that while Ca 21 ionophore treatment rapidly arrested cell expansion of root hairs, secretion of wall material was sustained, leading to a thickening in which tip growthrelated secretion normally occurs. YFPTRabA4b is thought to mark the apical secretory vesicle machinery in growing Arabidopsis root hairs, dissipating once growth ceases (Preuss et al, 2004(Preuss et al, , 2006. Monitoring the distribution of this yellow fluorescent protein (YFP) marker in root hairs revealed that, as reported previously, RabA4b decorated an apical accumulation of vesicles (Fig.…”
Section: Increasing the Tip-high Ca 21 Gradient Arrests Growthmentioning
confidence: 64%
See 1 more Smart Citation
“…These observations indicate that while Ca 21 ionophore treatment rapidly arrested cell expansion of root hairs, secretion of wall material was sustained, leading to a thickening in which tip growthrelated secretion normally occurs. YFPTRabA4b is thought to mark the apical secretory vesicle machinery in growing Arabidopsis root hairs, dissipating once growth ceases (Preuss et al, 2004(Preuss et al, , 2006. Monitoring the distribution of this yellow fluorescent protein (YFP) marker in root hairs revealed that, as reported previously, RabA4b decorated an apical accumulation of vesicles (Fig.…”
Section: Increasing the Tip-high Ca 21 Gradient Arrests Growthmentioning
confidence: 64%
“…Indeed, the structures of the apical actin cytoskeleton and its regulatory proteins (villins, gelsolins, and actin-depolymerizing factors; Smertenko et al, 1998;Tominaga et al, 2000;Allwood et al, 2001;Ketelaar et al, 2003;Fan et al, 2004) are thought to be regulated by the tip-high Ca 21 (Yokota et al, 2005). Similarly, there is evidence that annexins (Blackbourn et al, 1992;Clark et al, 1992;Carroll et al, 1998), phosphoinositide metabolism (Preuss et al, 2006), and calmodulin and protein kinases (Moutinho et al, 1998;Yoon et al, 2006) also play roles in sustaining tip growth and are regulated via the cytosolic Ca 21 gradient.…”
mentioning
confidence: 99%
“…In this regard, overexpression or down-regulation of a type B phosphatidylinositol-4-phosphate 5-kinase 3, which regulates endogenous phosphatidylinositol-4,5-bisphosphate levels, leads to deformed root hairs (Kusano et al, 2008;Stenzel et al, 2008). Further support for the interdependence of lipid signaling and small GTPases in root hair growth comes from the observation that RabA4b recruits phosphatidyl 4-OH kinase to the growing root hair tip and that knockouts of this gene induced the formation of wavy root hairs similar to agd1 (Preuss et al, 2006). More recently, the root hair defective4 (rhd4) mutant, which has short, branched, and bulged root hairs, was shown to be disrupted in a gene encoding a phosphoinositide phosphatase that regulates the levels of phosphatidylinositol-4-phosphate (Thole et al, 2008).…”
Section: Discussionmentioning
confidence: 90%
“…Small GTPases also have been shown to coordinate tip growth via their interaction with lipid signaling pathways. In Arabidopsis root hairs, for example, RabA4b specifically interacts with a phosphatidylinositol 4-OH kinase at the tip, and this interaction has been proposed to be relevant for maintaining the cytoplasmic calcium gradient that drives polar root hair growth (Preuss et al, 2006). In this regard, inhibiting the production of lipid signaling molecules such as phosphatidic acid disrupted tip growth, disorganized the actin cytoskeleton, and dissipated the tip-focused cytoplasmic calcium gradient (Potocký et al, 2003;Monteiro et al, 2005;Motes et al, 2005).…”
mentioning
confidence: 99%
“…Additional evidence of a connection between Rab proteins and polar growth comes from the characterization of a member of the Arabidopsis RABA4 subclass, RABA4b, which localizes to the trans-Golgi network compartment in the tip of growing root hairs (Preuss et al, 2004). Even though no phenotype was observed in RABA4b mutants, this protein has been implicated in tip growth in root hairs via its interaction with phosphatidylinositol-4-kinases, which are essential for root hair morphogenesis (Preuss et al, 2006). While Nod factor perception by the root hair cell leads to root hair curling and IT formation, the molecular mechanisms underlying these processes are largely unknown.…”
Section: Introductionmentioning
confidence: 99%